Associations between arterial health and sexual function in women aged 60–64 years - Viivi Virkkunen; Katja Kero; Mari Koivisto; Teemu Niiranen; Olli Heinonen; Sari Stenholm; Päivi Polo‐Kantola (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Female sexual dysfunction is very common, but its determinants remain under‐investigated. Vasculogenic impairments are suggested to be related to female sexual dysfunction, but previous literature regarding the association is scarce. This study aims to study the association between arterial health and female sexual function in women in their 60s. Material and methods The sample for this cross‐sectional study comprised 117 women (aged 60–64 years) who participated in the Finnish Retirement and Aging study. Arterial health was measured according to the participants' pulse wave velocity, ankle–brachial index, blood pressure, and pulse pressure. Sexual function was measured using the Female Sexual Function Index, which resulted in a total score and six sub‐scores. Associations were examined using multivariable regression analyses, which were adjusted for age, relationship happiness, systemic menopausal hormone therapy and/or local estrogen, smoking, alcohol risk use, body mass index, and depressive symptoms. Results Higher diastolic blood pressure was associated with a higher total Female Sexual Function Index score (β = 0.24, 95% confidence interval [CI] 0.07–0.41) and with higher desire (β = 0.02, 95% CI 0.01–0.04), arousal (β = 0.04, 95% CI 0.01–0.08), lubrication (β = 0.04, 95% CI 0.002–0.08), satisfaction (β = 0.03, 95% CI 0.003–0.05), and pain (β = 0.06, 95% CI 0.02–0.10) sub‐scores. Also, higher ankle–brachial index was associated with higher satisfaction sub‐score (β = 2.10, 95% CI 0.44–3.73) and lower pulse pressure was associated with higher orgasm sub‐score (β = 0.03, 95% CI 0.0002–0.06). Other associations between ankle–brachial index and Female Sexual Function Index scores were statistically insignificant, but considering the magnitude the findings may imply clinical significance. Systolic blood pressure and pulse wave velocity were not associated with sexual function. Conclusions This study suggested a plausible association between higher diastolic blood pressure and female sexual function, but considering clinical significance our findings suggest an association between higher ankle–brachial index and good sexual function in women in their 60s.